Muscular damage and intravascular haemolysis during an 18 hour subterranean exploration in a cave of 700 m depth. Issue 3 (27th February 2006) - Stenner, E; Gianoli, E; Biasioli, B; Piccinini, C; Delbello, G; Bussani, A
Abstract : Objective: To verify presence and severity of muscular and/or intravascular damage during a subterranean exploration of long duration. Methods: We measured serum levels of creatine kinase (CK) and lactate dehydrogenase (LDH) as markers of muscular damage. We also measured haptoglobin as a marker of intravascular haemolysis, and platelets and leucocytes as markers of inflammation. Results: We found in all the participants an increase in CK, LDH, and platelets and leucocytes (mainly due to neutrophilia and monocytosis), and a decrease in the level of haptoglobin and circulating lymphocytes. Conclusions: The observed data suggest that continuous effort during long alpine subterranean explorations, environmental conditions, sleep deprivation, multiple impacts on rocks, and compression caused by bindings of the caving harness cause muscle damage, intravascular haemolysis, inflammation response, and immunological changes.